2009
DOI: 10.1002/pits.20430
|View full text |Cite
|
Sign up to set email alerts
|

Types and treatment of pediatric sleep disturbances

Abstract: This article provides an overview of pediatric sleep disturbances with emphases on types and treatments. Relationships between sleep disorders and comorbid conditions function to exacerbate and maintain both disorders. An estimated 20% of teenagers experience chronic partial sleep deprivation, resulting in problems with memory, attention, and behavior control. Treatment of choice for chronic partial sleep deprivation involves a comprehensive approach to regularizing the adolescent's sleep -wake schedule. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…A prevalência dos distúrbios de sono na infância e adolescência é estimada entre 20% e 30% 20 . Os adolescentes investigados apresentaram prevalência de 53,6% de baixa duração de sono, sendo superior aos 20% identificados em adolescentes residentes em zonas rurais do Sul do Brasil 14 e aos 15,5% identificados em adolescentes europeus 21 .…”
Section: Discussionunclassified
“…A prevalência dos distúrbios de sono na infância e adolescência é estimada entre 20% e 30% 20 . Os adolescentes investigados apresentaram prevalência de 53,6% de baixa duração de sono, sendo superior aos 20% identificados em adolescentes residentes em zonas rurais do Sul do Brasil 14 e aos 15,5% identificados em adolescentes europeus 21 .…”
Section: Discussionunclassified
“…As a result, research has demonstrated the utility of a number of these agents for the partial remediation of the signs and symptoms of many childhood disorders. In the preceding articles, advances in the pharmacological treatment of ADHD (see Vaughan, Roberts, & Needelman, 2009); bipolar disorder, schizophrenia, and other psychotic disorders (see Noggle & Dean, 2009a); depressive disorders (see Noggle & Dean, 2009b); sleep disturbances (see Hamilton, 2009); seizures and epilepsy (see Titus & Thio, 2009); and pervasive developmental disorders (see Floyd & McIntosh, 2009;Noggle & Dean, 2009a) have been discussed. In addition, issues pertaining to the changing role of psychological professionals within the schools have been offered.…”
Section: Southern Illinois University School Of Medicinementioning
confidence: 99%